(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
This study was designed to test the psychometric properties of the Chinese interRAI Intellectual Disability (ID) tool in a Chinese population with learning disabilities in Hong Kong. The Chinese interRAI ID was prepared based on the original interRAI ID which is a standardized, comprehensive instrument and is designed to evaluate the strengths, preferences, and needs of persons with all levels of ID living in various care settings. A sample of 100 people with moderate to severe intellectual disabilities was assessed with the Chinese interRAI ID and its criterion measures. The subscales of the interRAI ID, including the Cognitive Performance Scale, Depression Rating Scale, Aggressive Behavior Scale, Activities of Daily Living Hierarchy Scale, and Instrumental Activities of Daily Living Involvement Scale, had high internal consistency (Cronbach’s α = .66 to .87) and test–retest reliability (r = .96 to .99; κ = .68 to .81). Comparison of the interRAI ID scales with criterion measures supported concurrent and discriminant validity of these scales. The study results provide preliminary support for the Chinese interRAI ID as a reliable and valid tool for assessing Chinese individuals with learning disabilities in Hong Kong.